AB0845 The effect of biologic disease-modifying antirheumatic drugs patient reported outcomes in patients with axial spondyloarthritis; a systematic literature review and a call for action. (12th June 2018) - Rodrigues-Manica, S.; Leite Silva, J.; Machado, A.R.; Coelho, C.; Duarte, J.; Vieira-Sousa, E.; Tavares-Costa, J.; Pimentel-Santos, F.M.
Abstract : Background: Patient reported outcomes (PROs) have gained relevance in the evaluation of several diseases such as axial spondyloarthritis (axSpA). They allow the clinician to have a quantitative measurement of several aspects of the disease, according to the patient perspective. Objectives: In this review we intended to evaluate the efficacy of different biologic disease-modifying anti-rheumatic drugs (bDMARD) in achieving the minimum clinically important difference (MCID) in several PROS's. Data from randomised controlled trials (RCT) conducted in radiographic axSpA (r-axSpA) and non-radiographic axSpA (nr-AxSpA) patients were included. Methods: A systematic literature review (SLR) was performed using the MEDLINE database (August 17 2017) with the filters "published in the last 10 years" and "humans". Abstracts from the EULAR 2017 were also considered. The PICO (P, population; I, intervention; C, comparison; O, outcome) concept was used to perform the analysis according to: Patients: adults (>18 years old) with r-axSpA or nr-axSpA; Intervention: any bDMARD regardless of formulation or duration; Comparison: placebo and/or any different drug; Outcomes: The Bath Ankylosing Spondylitis Functional Index (BASFI), the Ankylosing Spondylitis Quality of Life (ASQoL), the EuroQol-5D (EQ-5D), the Short Form 36 Health Survey physical component summary (SF36-PCS), the Short Form 36 Health Survey mental component summary (SF36-MCS), and the Functional Assessment of Chronic Illness Therapy – Facit (FACIT-F). For each outcome we assessed whether the treatment group was superior, equal or inferior to the placebo (PBO) group regarding the achievement of the MCID of the assessed PRO over time. Results: After screening 557 references (after de-duplication), 16 RCTs were included, studying interleukin 17 inhibitors (IL17i) and tumour necrosis factor inhibitors (TNFi). In r-axSpA, the treatment group (for both TNFi and IL17i) reached the MCID for all the assessed PROs, except for a single study in which both the treatment and PBO groups reached the MCID for the SF36-PCS. For nr-axSpA the results were more heterogeneous (table 1). Conclusions: The assessment of PROs in RCT is scarce. The profile of PROs response seems to be different between r-axSpA and nr-axSpA patients; these differences must be further validated in future trials. This study launches a call for action in PROs reporting standardisation. References: [1] -Deodhar 2016; van der Heijde2009; Sieper 2013; Haibel 2008; Maksymowych 2008; Dougados 2014; Maksymowych 2016; Dougados 2015; van der Heijde 2014; Deodhar Abstract THU0348. EULAR 2017; Reveille JD EULAR 2017; Park W 2016; Sieper 2014; Deodhar 2016; Marzo-Ortega 2017; Kvien TK Abstract THU0393 EULAR 2017; Sieper 2015. Acknowledgements: Novartis Pharma for the logistic support. Disclosure of Interest: S. Rodrigues-Manica: None declared, J. Leite Silva: None declared, A. R. Machado: None declared, C. Coelho Employee of: Novartis Pharma Portugal, J. Duarte Employee of: Novartis Pharma Portugal, E. Vieira-Sousa: None declared, J. Tavares-Costa: None declared, F. M. Pimentel-Santos: None declared